Variasi Kadar AvicelPH101 dan Aerosil Terhadap Kadar Air Serbuk Bunga Telang (Clitoria ternatea L.) - ima fitria lestari; Erma Pujiawati; Muhammad Rofik Usman (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Abstract Background: Banyuwangi has the potential of diverse natural resources. One example of the potential plant that can be utilized is butterfly pea (Clitoria ternatea L.). The contents of butterfly pea are phenolic acids, stilbenes (phytoalexins), flavanols, anthocyanins, flavonols and flavanones, polyphenols and flavonoids. In this research, preparations were developed from butterfly pea extract into powder form to make it more practical. The problems occur in making formulations usually have physical characteristics of being thick or liquid making it difficult to formulate into solid dosage forms, so in its manufacture additional ingredients or adsorbents were needed to dry the extract so it is easy to formulate. Avicel pH 101 and aerosil is a combination used as an adsorbent in the manufacture of powders. Aim: This study aimed to determine the effect of Avicel PH101 and Aerosil variations through the results of evaluating the moisture content of butterfly pea ethanol extract powder. Method: This study was a laboratory experiment that began with maceration of butterfly pea simplicia using 70% ethanol and then evaporated to obtain a thick extract of butterfly pea. The preparation of butterfly pea powder was carried out using a combination of Avicel pH 101 and aerosil which was varied in four formulas, namely FI (20%:20%), FII (50%:20% ), FIII (90%:0%), FIV (90% :20%) ). Results: The evaluation results of the water content test that met the requirements were FII(50%:20%) with a moisture content of 2.4%, FIII(90%:0%) with a moisture content of 2.8% and FIV (90%;20%) was the most optimal formulation of Avicel PH101 and Aerosil combination for the manufacture of butterfly pea powder with a moisture content of 1.5% and organoleptically in the form of a powder obtained was very dry and delicate. Keywords: Aerosil, Avicel PH101, Butterfly Pea Powder, Moisture Content.